2022
DOI: 10.1086/716346
|View full text |Cite
|
Sign up to set email alerts
|

Did Timing Matter? Life Cycle Differences in Effects of Exposure to the Great Recession

Abstract: The research program of the Center for Economic Studies (CES) produces a wide range of economic analyses to improve the statistical programs of the U.S. Census Bureau. Many of these analyses take the form of CES research papers. The papers have not undergone the review accorded Census Bureau publications and no endorsement should be inferred. Any opinions and conclusions expressed herein are those of the author(s) and do not necessarily represent the views of the U.S. Census Bureau. All results have been revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…We also contribute to the literature on the effect of involuntary displacement on individual's labor market and life outcomes (e.g., Rege et al 2009;Sullivan and von Wachter 2009;Browning and Heinesen 2011;Del Bono et al 2012;Tanndal et al 2020;Coelli 2011;Minaya et al 2020;Salvanes et al 2022), as well as the impact of parental job loss on children (e.g., Oreopoulos et al 2008;Rege et al 2011;Hilger 2016;Huttunen et al 2020;Mörk et al 2020;Tanndal and Päällysaho 2020;Willage and Willén 2022). Closely related to our paper is the smaller literature on the causal effect of shocks across the life cycle (e.g., Salvanes et al 2022;Rinz 2021), and how workers' professional and personal lives are impacted by adverse labor shocks (e.g., Davis and von Wachter 2011;Oreopoulos et al 2012;Adda et al 2013). These studies provide novel insights into the effects of shocks on workers' careers across their life cycles, but they do not examine how children of different ages are impacted by such shocks.…”
mentioning
confidence: 59%
“…We also contribute to the literature on the effect of involuntary displacement on individual's labor market and life outcomes (e.g., Rege et al 2009;Sullivan and von Wachter 2009;Browning and Heinesen 2011;Del Bono et al 2012;Tanndal et al 2020;Coelli 2011;Minaya et al 2020;Salvanes et al 2022), as well as the impact of parental job loss on children (e.g., Oreopoulos et al 2008;Rege et al 2011;Hilger 2016;Huttunen et al 2020;Mörk et al 2020;Tanndal and Päällysaho 2020;Willage and Willén 2022). Closely related to our paper is the smaller literature on the causal effect of shocks across the life cycle (e.g., Salvanes et al 2022;Rinz 2021), and how workers' professional and personal lives are impacted by adverse labor shocks (e.g., Davis and von Wachter 2011;Oreopoulos et al 2012;Adda et al 2013). These studies provide novel insights into the effects of shocks on workers' careers across their life cycles, but they do not examine how children of different ages are impacted by such shocks.…”
mentioning
confidence: 59%
“…Since the 1990s, Black workers are more likely to have been displaced from their jobs than White workers (Wrigley-Field & Seltzer, 2020). During the Great Recession, losses among Black workers about 40% greater than other racial groups (although men experienced greater losses compared to women) (Rinz, 2019). Using a nationally representative sample of families with children from the 2004 and 2008 panels of the Survey of Income and Program Participation (SIPP), Gennetian and colleagues found that across race and ethnicity, children in lowerincome families experienced greater income volatility than their higher-income peers, but at the lowest income levels, Hispanic children were slightly more likely to experience stable incomes than their peers (Gennetian et al, 2019).…”
Section: Racial and Ethnic Disparities In Economic Vulnerabilitymentioning
confidence: 99%
“…While previous studies find that employer and occupational characteristics play a role in explaining recession-induced penalties (see, for example, Oyer, 2006, Oyer, 2008, Oreopoulos et al, 2012, and Rinz, 2019, the precise magnitude of employer effects' role in generating scars for recessionary entrants remains unknown. Our second contribution is to provide the first quantitative estimate of the relative importance of employer-specific factors in driving the recession-induced earnings penalty.…”
Section: Introductionmentioning
confidence: 98%